Protaetia (Potosia) jelineki (Coleoptera: Scarabaeidae: Cetoniinae: Cetoniini): preimaginal stages, biology, intrapopulation variability and taxonomy - Uliana, Marco; Vas’ko, Bogdan; Polat, Alper (Zootaxa, 2019)
Protaetia (Potosia) jelineki (Petrovitz, 1981) is a little-known flower beetle from north-eastern Turkey whose taxonomy and nomenclature have been recently treated by different authors, coming to opposite conclusions. Following the opportunity to observe and sample a dense population from the outskirts of Erzurum, we add different contributions to the knowledge of this taxon. Larva and pupa are described and illustrated. An account on the intrapopulation variation of adults is provided, thus adding relevant information to the problematic diagnosis from close taxa: presence or absence of white dorsal pattern and of pygidial impressions are not to be considered diagnostic towards P. hajastanica Ghrejyan & Kalashian, 2017; and the usually peculiar elytral sculpture may show considerable variation. We discuss the uncertain identity of the only known syntype of Cetonia floricola fausti Kraatz, 1891, which is involved in the taxonomic and nomenclatorial debate, and we consider it conspecific with P. splendidula (Faldermann, 1835), following also the introduction of a new morphometric character allowing to diagnose P. jelineki from P. splendidula based on the shape of anterior tibiae. We provide information about the natural history of P. jelineki based on observation in nature and captivity. Adults are often associated to flowering plants of Crambe orientalis and can be active during at least two seasons.